CALLUS INDUCTION IN Kappaphycus alvarezii USING INDOLE-3-ACETIC ACID (IAA) and 6-BENZYLAMINOPURINE (BAP) FOR SEEDSTOCK DEVELOPMENT - Mulyono, Mugi; Salsabila, Mutia Safa; Rasnijal, Muhammad; Fadilah, Siti; Putra, Angkasa (Indonesian Aquaculture Journal, 2025)
The commercially important red seaweed Kappaphycus alvarezii is extensively cultivated for carrageenan production. Despite its economic value, large-scale reproduction and genetic enhancement remain limited due to its low regeneration potential. This study aimed to optimize plant growth regulator (PGR) concentrations for efficient callus induction in K. alvarezii. A completely randomized design was employed, comprising five treatments with varying concentrations of indole-3-acetic acid (IAA) and 6-benzylaminopurine (BAP), along with a control lacking PGRs. A total of 180 explants from meristematic tissues of acclimatized thalli were cultured (30 explants per treatment). The highest callus induction rate (88%) was achieved with 1.50 mg/L IAA and 5 mg/L BAP (Treatment F), with visible callus formation beginning around day 38. A progressive color change from brown to white was observed, indicating active cellular proliferation. Other treatments exhibited lower induction rates, ranging from 0% (control) to 61% (Treatment D). These findings underscore the critical influence of auxin–cytokinin interactions on callogenesis and offer an optimized hormonal regime for improving in vitro culture efficiency. The established protocol provides a valuable platform for future large-scale propagation and genetic improvement strategies in K. alvarezii, contributing to the advancement of seaweed biotechnology.